Dialects of Violence: Unveiling the Artistic Response to Partition: A Literary Exploration (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The dialectics of violence, particularly characterizing the partition of the sub-continent, indeed exercised many a creative soul to articulate an artistic response to the life event. The contours of this creative endeavour, in fact, parallel the multiple manifestations of this phenomenon in actuality that constantly and with an ever increasing intensity explodes through the fluid and yet uncrystallised socio-cultural and political matrix of India. The reflective representation and the creative comprehension of partition within the literary construct presupposes an organising poetics--structuration of the processes of meaning to understand and foreground the epistemological and ontological potentials/implications of the socio-cultural reality embedded in the narrative contestations of partition. This, at best, in the bulk of partition fiction in English, is provided by structuring of the discourse through binary aesthetics. It implies the construction of meaning by making a difference, a distinction within a system of opposites and contrasts.